1996
DOI: 10.1109/22.539947
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic absorption in the human head and neck for mobile telephones at 835 and 1900 MHz

Abstract: Stereoselective Synthesis of (E)-α,β-Dehydroamino Acid Esters. -The presented method gives access to the E-isomers of α,β-dehydroamino acid esters in high yields and is complementary to the existing methods for the preparation of the thermodynamically more stable Z-isomers. The E/Z ratio depends on the reaction conditions as well as on the substituents and protecting groups on the substrates. The best results are obtained by using NaI as additive for aryl-substituted substrates and MgBr 2 ·Et 2 O or ZnCl2 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
231
0
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(250 citation statements)
references
References 9 publications
12
231
0
7
Order By: Relevance
“…In recent years, work has been presented regarding mobile communications equipment (MCE) positioned near the ear [3][4][5][6]. The head has also been irradiated from in front of the eye using realistic mobile phone models [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, work has been presented regarding mobile communications equipment (MCE) positioned near the ear [3][4][5][6]. The head has also been irradiated from in front of the eye using realistic mobile phone models [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A rigorous Finite-Difference Time-Domain (FDTD) model is used. In recent years some work has been written up regarding mobile phones positioned near the ear [1][2][3][4]. The head has also been irradiated from in front of the eye using realistic mobile phone models [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [1 -4] it has been demonstrated that metallic spectacles can alter the specific absorption rate in the head and in particularly in the eyes. In recent years some work has been written up regarding mobile phones positioned near the ear [5][6][7][8]. Illumination has been considered from in front of the eye using realistic mobile phone models [7][8][9].…”
Section: Introductionmentioning
confidence: 99%